Respostas
respondido por:
1
10y-5(1+y)=3(2y-2)-20 pliss
10y - 5 - 5y = 6y - 6 - 20
10y - 5y - 5 = 6y - 26
5y - 5 = 6y - 26
5y - 5 - 6y = - 26
5y - 6y = - 26 + 5
-1y = - 21
y = - 21/-1
y = + 21/1
y = 21 ( resposta)
10y - 5 - 5y = 6y - 6 - 20
10y - 5y - 5 = 6y - 26
5y - 5 = 6y - 26
5y - 5 - 6y = - 26
5y - 6y = - 26 + 5
-1y = - 21
y = - 21/-1
y = + 21/1
y = 21 ( resposta)
respondido por:
0
Resposta:
y = 21
Explicação passo-a-passo:
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás